FNDC3B promotes gastric cancer metastasis via interacting with FAM83H and preventing its proteasomal degradation - Yuying Zhang; Lingyu Ran; Yuying Liu; Wei Li; Ai Ran; Haiping Li; Bo Huang; Junwu Ren; Hao Ning; Qiang Ma; Xiaolin Wang; Feifei Yang; et al. (Cellular & Molecular Biology Letters)
Abstract Background Gastric cancer (GC) is one of the most prevalent digestive tract malignancies, with metastasis being a major contributor to poor prognosis in patients. Fibronectin type III domain-containing 3B (FNDC3B) plays pivotal roles in various tumors, yet its role in GC remains unknown. Methods We utilized a GC immunohistochemistry (IHC) chip and specimens to identify high expression of FNDC3B in GC. In vitro cellular experiments and in vivo nude mouse models were constructed to validate the biological functions of FNDC3B. Truncated mutants of FNDC3B and immunofluorescence (IF) assays were conducted to explore the critical domains of FNDC3B. Liquid chromatography-tandem mass spectrometry (LC–MS) and coimmunoprecipitation (Co-IP) were employed to screen and identify target proteins interacting with FNDC3B. Rescue experiments were performed to uncover interactions between FNDC3B and the binding protein. Results FNDC3B was found to function as an oncogene in GC. Clinically, FNDC3B was significantly upregulated in GC specimens and associated with poor survival in patients with GC. Functionally, elevated FNDC3B promoted GC metastasis both in vitro and in vivo. Structurally, the proline-rich N-terminus and a transmembrane (TM) domain at the C-terminus were crucial for maintaining the metastasis function of FNDC3B. Mechanistically, FNDC3B interacted with FAM83H, inhibiting the ubiquitin–proteasome degradation of FAM83H, which in turn enhanced GC progression through the FNDC3B/FAM83H/Snail/EMT axis. Conclusions Our results demonstrate that FNDC3B promotes GC metastasis and has the potential to serve as a therapeutic target for GC.